Eloka-Té : Village cooperative in Ebrié country (lower Ivory Coast) - (:unkn) unknown (My University, 1967)
This thesis examines the exceptional case of the agricultural cooperative of Eloka-Té in Ébrie country, which survived the collapse of the Ivorian cooperative system, unlike the majority of cooperatives created since 1959. The study covers the period 1959-1967 in the post-independence context. The author demonstrates that the general failure of the cooperative system stems from the inadequacy of European models imposed by the national organization (CNCMA and CCCA). These organizations, by prioritizing commercialization over production, maintained cooperatives in dependence and prevented their self-development.The Eloka-Té cooperative succeeded in developing autonomously after 1963 through its adaptation to traditional Ébrie social structures. Ébrie society, characterized by weak hierarchization and organization into age classes, allowed for the harmonious integration of the cooperative by preserving certain aspects of tradition, thus avoiding the conflicts observed elsewhere. This geographical research emphasizes the importance of local knowledge for assessing the chances of success of development initiatives from outside, while demonstrating the limits of standardized approaches in post-colonial African contexts
Keywords: African Research